The Result of Using Games to Develop Chinese Communication Skills - สุขใจรุ่งวัฒนา, ไพศาล (Thai Journal of East Asian Studies, 2020)
This research is to study the effects of games to improve Chinese communication skills. Objectives are to (1) compare the improvement of students before and after learning by using games in the Chinese language class, and (2) to assess the satisfaction of students about the class. There are 35 students. Statistical data analysis use percentage, average, standard deviation, and t-test. The average score of the Chinese language before testing is 16.51, and the standard deviation is 1.01. After testing, the average score is 27.77, and the standard deviation is 1.73. Paired sample t-test is -6.638. That means learning by using games in the class, has improved Chinese communication skills. It is statistical significance when alpha set to 0.05. The average satisfaction of input, process, and output about learning by using games in the Chinese language class is 3.73, 4.23, and 4.27, respectively. The standard deviation of satisfaction of input, process, and output is 0.67, 0.64, and 0.59, respectively.